Inhibition of mammalian target of rapamycin reduces epileptogenesis and blood-brain barrier leakage but not microglia activation - van Vliet, Erwin A.; Forte, Grazia; Holtman, Linda; den Burger, Jeroen C. G.; Sinjewel, Arno; de Vries, Helga E.; Aronica, Eleonora; Gorter, Jan A. (Epilepsia (Copenhagen), 2012)
Summary Purpose:  Previous studies have shown that inhibition of the mammalian target of rapamycin (mTOR) pathway with rapamycin prevents epileptogenesis after pharmacologically induced status epilepticus (SE) in rat models of temporal lobe epilepsy. Because rapamycin is also known for its immunosuppressant properties we hypothesized that one of the mechanisms by which it exerts this effect could be via suppression of brain inflammation, a process that has been suggested to play a major role in the development and progression of epilepsy. Methods:  Rats were treated with rapamycin or vehicle once daily for 7 days (6 mg/kg/day, i.p.) starting 4 h after the induction of SE, which was evoked by electrical stimulation of the angular bundle. Hereafter rapamycin was administered every other day until rats were sacrificed, 6 weeks after SE. Video‐electroencephalography was used to monitor the occurrence of seizures. Neuronal death, synaptic reorganization, and microglia and astrocyte activation were assessed by immunohistologic staining. Fluorescein was administered to quantify blood–brain barrier leakage. Key Findings:  Rapamycin treatment did not alter SE severity and duration compared to vehicle treatment rats. Rapamycin‐treated rats developed hardly (n = 9) or no (n = 3) seizures during the 6‐week treatment, whereas vehicle‐treated rats showed a progressive increase of seizures starting 1 week after SE (mean 8 ± 2 seizures per day during the sixth week). Cell loss and sprouting that normally occur after SE were prominent but on average significantly less in rapamycin‐treated rats versus vehicle‐treated rats. Nevertheless, various inflammation markers (CD11b/c and CD68) were dramatically upregulated and not significantly different between post‐SE groups. Of interest, blood–brain barrier leakage was barely detected in the rapamycin‐treated group, whereas it was prominent in the vehicle‐treated group. Significance:  mTOR inhibition led to strong reduction of seizure development despite the presence of microglia activation, suggesting that effects of rapamycin on seizure development are not due to a control of inflammation. Whether the effects on blood–brain barrier leakage in rapamycin‐treated rats are a consequence of seizure suppressing properties of the drug, or contribute to a real antiepileptogenic effect still needs to be determined.